ANALISIS DAYA SAING KARET ALAM INDONESIA DAN VARIABEL-VARIABLA YANG MEMPENGARUHINYA - Befri Apriansyah (Jurnal Statistika Universitas Muhammadiyah Semarang, 2019)
Exports are an important factor in economic growth. Natural rubber is one of the 7th highest export of all commodities in Indonesia in 2016. Natural rubber is a commodity with the average share to total export of plantation sector of 29.8% per year. Indonesia is one of the largest natural rubber exporting countries in the world besides Thailand. However, Indonesia's export ratio to natural rubber production has experienced a downward trend since 1999 and the average share of Indonesia's exports to the world's total natural rubber exports is still below the share of Thailand's natural rubber exports. This research performs descriptive analysis with graphs and inferential analysis with Error Correction Mechanism (ECM) analysis method. The results show that in the period 1989 to 2005 Thailand's natural rubber competitiveness surpassed Indonesia and in the period 2006 to 2016 except 2009, the competitiveness of natural rubber Indonesia is able to surpass Thailand. In the long period, the significant variables on RCA of Indonesian natural rubber are natural rubber productivity and RCA of Thailand's natural rubber. While in the short term, significant variable on RCA growth of Indonesian natural rubber are the growth of Thailand’s RCA.